KAJIAN HIDROSTATIK KAPAL OPERASIONAL KAMPUS USN KOLAKA (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2022)
The development of the University of Nineteen November Kolaka campus located in Central Buton Regency has its own challenges due to the separation of the two campuses by the ocean. The utilization of a reliable sea transportation fleet needs to be developed to facilitate access and coordination with the main campus. Initial ship planning has been made by taking into account the design factors and ship production costs (Mubarak et al, 2021), but has not yet carried out ship modeling and ship calculations using the help of related software. This study aims to determine the hydrostatic characteristics of the ship and calculate the resistance of the design ship. The results showed that with a ship length of 14.5 m, width of 3.2 m, height of 1.5 m, it will have a ship resistance of 11.8 kN and a displacement of 6910 kg calculated at a ship depth of 0.45 m, a ship resistance of 14.2 kN and a displacement of 10408 kg calculated at a ship depth of 0.55 m, a ship resistance of 16.7 kN and a displacement of 13984 kg calculated at a ship depth of 0.65m.